PENGARUH PERSEPSI KEMUDAHAN DAN PERSEPSI KEGUNAAN TERHADAP NIAT MENGGUNAKAN OVO DENGAN SIKAP SEBAGAI VARIABEL MEDIASI DI DENPASAR - Primananda, Pande Gde Bagus Naya; Kusuma, AA Made Indra Wijaya; Brahmanta, Ida Bagus Angga (JURNAL LENTERA BISNIS, 2026)
The development of financial technology has transformed the way people conduct financial transactions from conventional methods to digital payment systems. One of the widely used digital wallet services in Indonesia is OVO. Although the number of users continues to increase, the actual intention to use the application is influenced by several psychological factors of users. This study aims to analyze the effect of perceived ease of use and perceived usefulness on intention to use OVO with attitude as a mediating variable. This research employed a quantitative approach with an explanatory research design. The sample consisted of 105 respondents who were OVO users in Denpasar selected using purposive sampling. Data were collected through questionnaires using a Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that perceived ease of use significantly influences perceived usefulness. Perceived usefulness significantly affects attitude and intention to use OVO, while attitude also has a significant effect on intention to use OVO. However, perceived ease of use does not significantly affect attitude. The mediation analysis shows that attitude mediates the relationship between perceived usefulness and intention to use OVO but does not mediate the relationship between perceived ease of use and intention. These findings suggest that the perceived benefits of digital payment applications play a key role in encouraging users’ intention to use digital wallets.